Determination of Mineral Oil‐Saturated Hydrocarbons (MOSH) in Vegetable Oils by Large Scale Off‐Line SPE Combined with GC‐FID. (23rd December 2016) - Li, Bingning; Wu, Yanwen; Liu, Lingling; Ouyang, Jie; Ren, Jiajia; Wang, Yu; Wang, Xinxin
Abstract: A method based on an off‐line large‐scale solid phase extraction (SPE) approach combined with conventional gas chromatographic‐flame ionization detection (GC‐FID) was developed to determine the mineral oil‐saturated hydrocarbons (MOSH) in vegetable oils. A large‐scale SPE column loaded with 10 g of activated silica gel impregnated with 1% silver nitrate which was used to retain lipids and olefins in vegetable oils and the MOSH in the oil samples was eluted with hexane. Then 2 μL concentrated solution was splitlessly injected into a common GC‐FID instrument. The quantification limit reached 2.5 mg/kg when the MOSH fraction was concentrated to 0.1 mL. The accuracy of this procedure, as assessed by measuring the recoveries from spiked oil samples, was higher than 80%. This procedure was applied to analyze the MOSH in 38 commercial vegetable oils from Chinese market, which was the first survey of mineral oil contaminant in Chinese edible oils. The oil samples contaminated with different levels of MOSH, among which, 15 samples contained no mineral oils and 3 samples were contaminated with more than 50 mg/kg of MOSH. The highest contamination level was found in one of rice oils, in which the concentration of MOSH was up to 713.36 mg/kg. Of the 9 types of oils analyzed, camellia oil contained MOSH ranging between 6.76 and 78.49 mg/kg, averaging 46.72 mg/kg, indicating a higher contamination level than other types of oils. The results suggested that it is necessary to routinely detect mineral oil contamination in vegetable oils for food safety.